Degradation of Benzothiophene and Related Compounds by a Soil Pseudomonas in an Oil-Aqueous Environment - Sagardía, Fermín (1975)
Pseudomonas aeruginosa PRG-1, an isolate from oil-contaminated soil, degrades benzothiophene (BT) and other related compounds in a 5% oil-basal medium system. The organism cannot grow on BT alone; 0.05% yeast extract is a suitable substrate for its growth and for its attack on BT. Although BT is partially toxic to the bacteria, toxicity is reduced when BT is added in this oil system. The oil phase is emulsified by bacterial action during the process. Oxygen uptake studies with washed cell suspensions show increased respiration in the presence of BT. Endogenous respiration is markedly decreased by p-hydroxy-mercuribenzoate, whereas respiration due to BT is scarcely affected, suggesting that oxygen is added directly to BT. Results obtained both in direct degradation and in respiration studies indicate that 3-methyl-thiophene is more rapidly and extensively degraded than BT and other related compounds.